Psikologi “Hijau” (Green Psychology) sebagai Alternatif untuk Peningkatan Kesejahteraan Psikologis Masyarakat Perkotaan - Murty Magda Pane (Bina Nusantara University, 2013)
This article describes so many disasters caused by the decrease of environment quality, or even pollution and environmental destruction, are due to society's bad behaviors. The decrease of environment quality, as consequences, may cause lower people's lives quality phisically and mentally as well. To overcome the problem, it is proposed a psychology intervension, called